2012
DOI: 10.1016/j.nimb.2011.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Rutherford backscattering analysis of porous thin TiO2 films

Abstract: The additional energy spread due to sample porosity was implemented in the SIM-NRA simulation code, version 6.60 and higher. Deviations of the path length and energy loss distributions from the ones expected from a Poisson distribution of the number of traversed pores are taken into account. These deviations are due to the interaction of pores at higher pore concentrations by overlap or blocking. The skewnesses of the energy distributions are approximated by two-piece normal distributions with identical first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Mayer et al showed [5] that for high density of spherical inclusions, non-Gaussian distributions are more appropriate. A similar argument can be made for columnar inclusions, and therefore the model implemented in NDF is valid for low densities.…”
Section: Model and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer et al showed [5] that for high density of spherical inclusions, non-Gaussian distributions are more appropriate. A similar argument can be made for columnar inclusions, and therefore the model implemented in NDF is valid for low densities.…”
Section: Model and Calculationsmentioning
confidence: 99%
“…In the presence of 2D and 3D structures, including inclusions, lateral heterogeneity, and surface and interface roughness, broad beam RBS measures an average of all the structures present in the area of the beam spot. This has been successfully utilised to make quantitative studies of roughness [1][2][3], inclusions [4,5], and even quantum dots [6] with RBS.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm of Stoquert & Szörenyi [193] allows the calculation of the effect of precipitates (density variation) on the spectra. DataFurnace [48] implements this algorithm and SIMNRA [194], implements a more accurate comparable algorithm. On the other hand, DataFurnace implements EBS resonances more correctly than SIMNRA (see Fig.6 and [47], and see the Intercomparison [171] XVIII The noun is spectrum; the adjective is spectral.…”
Section: Codes For Nuclear Reactionsmentioning
confidence: 99%
“…The physics basis, however, remained unchanged. New physics was implemented in version 6.10 and higher and was partly described in a number of publications [21,22,23,24], but these versions never became publicly available. SIMNRA 7 summarises all improvements of the simulation physics accumulated during the last years.…”
Section: Introductionmentioning
confidence: 99%